Overview of the United States' Immunization Program. (30th September 2021) - Roper, Lauren; Hall, Mary Ann Kirkconnell; Cohn, Amanda
Abstract: This manuscript describes the history, background, and current structure of the United States Immunization Program, founded upon public- and private-sector partnerships that include federal agencies, state and local health departments, tribal nations and organizations, healthcare providers, vaccine manufacturers, pharmacies, and a multitude of additional stakeholders. The Centers for Disease Control and Prevention sets the U.S. adult and childhood immunization schedules based on recommendations from the Advisory Committee on Immunization Practices. We review the current immunization schedules; describe the set of surveillance and other systems used to monitor the health impact, coverage levels, and safety of recommended vaccines; and note significant challenges. Vaccines have reduced the incidence of many diseases to historic lows in the US, and have potential to further reduce the burden of respiratory and other infectious diseases in the United States. Though the United States vaccination program has had notable successes in reducing morbidity and mortality from infectious disease, challenges—including disparities in access and vaccine hesitancy—remain. Supporting access to and confidence in vaccines as an essential public health intervention will not only protect individuals from vaccine-preventable diseases; it will also ensure the country is prepared for the next pandemic.